(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has made rapid developments in different sectors of the economy. Commerce is not an exception. The research seeks to establish Amazon, AliExpress, and eBay’s strategies, developments, and specific competitive advantages in the e-commerce industry. The research focuses on the financial, supply chain management, payment methods, and publicities sectors. The study uses a mixed-method approach in analyzing the three corporations as markets and marketplaces. Further, it employs quantitative time series analysis to examine the corporations’ internal and external markets. The study utilized disruption theory as its theoretical framework and the adoption commitment curve model as its conceptual framework. The research concludes that the three digital businesses have thrived because of various payment methods, programmatic targeting in publicity, utilization of technology in the supply chain, and enhancing customer trust and loyalty.